MENINGKATKAN KUALITAS PEMBELAJARAN MELALUI PENDAMPINGAN ASISTENSI MENGAJAR: Program Kampus Mengajar di SD Tunas Abadi Kota Jambi - Bradley Setiyadi; Nike Febryanti; Ghina Salsabila; Puteri Afsa Pradipta; Dheanisya Putri Asmarinda; Dhea Annisa Oktarizka; Attaya Arindra; Nimatuz Zahrak (Universitas Majalengka, 2022)
The “Kampus Mengajar” is a form of implementation of the “Merdeka Belajar Kampus Merdeka (MBKM)” in the form of teaching assistance in helping the learning process in elementary schools in various regions, one of which is SD Tunas Abadi which is located in Jelutung District, City of Jambi. In this program, the students involved have the responsibility to assist the school in the teaching and learning process, assist in technology adaptation, and assist administration. In addition, students have a responsibility to improve literacy and numeracy skills and increase student interest in learning during the pandemic. The result of this program is to increase the real role of universities in national development, especially in the field of education.